Difluorocarbene-based cyanodifluoromethylation of alkenes induced by a dual-functional Cu-catalyst. Issue 21 (15th February 2021) - Zhang, Min; Lin, Jin-Hong; Jin, Chuan-Ming; Xiao, Ji-Chang
Abstract : Described herein is a Cu-catalyzed difluorocarbene-based cyanodifluoromethylation of alkenes. BrCF2 CO2 Et and NH4 HCO3 serve as a carbon source and a nitrogen source of the nitrile group, respectively. The Cu-complex plays a dual role. Abstract : Although cyanofluoroalkylation has received increasing attention, a toxic cyanation reagent is usually required. Herein, a Cu-catalyzed difluorocarbene-based cyanodifluoromethylation of alkenes with BrCF2 CO2 Et/NH4 HCO3 under photocatalytic conditions is described. BrCF2 CO2 Et and NH4 HCO3 serve as a carbon source and a nitrogen source of the nitrile group, respectively, avoiding the use of a stoichiometric toxic cyanation reagent. The Cu-complex plays a dual role. It is not only a photocatalyst, but also a coupling catalyst for the formation of a C–CN bond.